Kemampuan Membaca Bahasa Jerman Melalui Metode Pembelajaran RSVP ( Review, Study, Verbalize, Preview ) - Ria Ashari; Muh Anwar (Phonologie : Journal of Language and Literature, 2023)
Abstract. The purpose of this study was to obtain information about improving German reading skills of class XI IPS 1 students of SMA Negeri 14 Gowa through the RSVP learning method. This type of research is classroom action research consisting of two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The subjects in this study were students of class XI IPS 1, totaling 35 students. The results of the students' reading test obtained an average score of 34.9 in cycle I and experienced an increase in cycle II with an average value of 42.4. This shows that the use of the RSVP learning method can improve the German reading ability of class XI IPS 1 students of SMA Negeri 14 Gowa.Keyword: Improvement, RSVP Learning Method, Reading